Blended Learning Solution of the Century - Hanna; Risma Ftiria Uky Yandini; Yulian Arpianto; Rizky Neguita Hanna (Global Writing Academica Researching and Publishing, 2023)
The real condition of the world today is in a phenomenon that brings governments to make a policy in the world of education. The distance learning policy (PJJ) during the COVID-19 pandemic, for example, turned out to be a new problem for education. The implementation of education and learning has undergone drastic changes. Learning is no longer using conventional face-to-face meetings, but is starting to be integrated with online learning. This paper aims to describe learning during a pandemic. This paper also shows that good collaboration between teachers, students, and parents can overcome problems in adapting blended learning methods during a pandemic. The application of the blended learning method in learning requires teachers to be creative in providing a learning platform. The activeness of students in the learning process and parents accompanying students during online learning greatly help the progress and creativity of students during the pandemic.